Psychopathic tendencies and mesolimbic recruitment by cues for instrumental and passively obtained rewards - Bjork, James M.; Chen, Gang; Hommer, Daniel W. (Biological psychology, 2012)
► Previous research indicates that impulsive persons have greater brain activation by rewards. ► We scanned controls with an fMRI task that probes mesolimbic activation by instrumental and passive rewards. ► Psychopathic tendencies correlated negatively with reaction time to targets to win rewards. ► Psychopathic tendencies correlated positively with mesolimbic recruitment by both instrumental and passive rewards. ► Psychopathy as a psychological construct may feature increased valuation of rewards. Psychopathy is a constellation of self-serving attitudes and antisocial behaviors with little regard to cost to self and others. Might this symptomatology arise in part from an exaggerated response of brain motivational circuitry to prospective rewards? We examined whether psychopathic tendencies are associated with increased recruitment of incentive neurocircuitry during anticipation of instrumental and conditioned rewards. Healthy controls completed the Psychopathic Personality Inventory (PPI), then were presented with response-contingent and passively delivered rewards during functional MRI. PPI scores correlated negatively with reaction time to incentivized targets, but not with reaction time to non-incentivized targets. PPI scores also correlated positively with recruitment of ventral striatum and anterior cingulate cortex during instrumental reward anticipation. PPI scores also correlated with middle frontal cortex recruitment during anticipation of passively received rewards. These data indicate that in psychiatrically healthy controls, individuals with greater endorsement of psychopathic tendencies show more robust neurophysiological and behavioral signatures of incentive motivation.